Two New γ Chain Variants: Hb F-Augusta GA [Gγ59(E3)Lys → Arg; HBG2: c.179A > G] and Hb F-Port Royal-II [Aγ125(H3)Glu → Ala; HBG1: c.377A > C]. (October 2014) - Kutlar, Ferdane; Ameri, Afshin; Patel, Niren H.; Zhuang, Lina; Johnson, Lee E.; Cheng, Michael L.; Kutlar, Abdullah
Abstract The total number of hemoglobin (Hb) variants so far reported to the HbVar database is 1598 (April 9 2014) and 130 of them are fetal Hb variants. Fetal Hb are categorized as two different subunits, Gγ- and Aγ-globin chains, and γ chain variants can be observed in both subunits. There are 72 Gγ- and 58 Aγ-globin chain variants. Most of them are clinically silent and detected during newborn screening programs in the USA and outside the USA. In this report, we discuss the molecular characteristics and diagnostic difficulties of two new γ-globin chain variants found in an African American baby with no clinical symptoms. One is a new Gγ-globin chain variant, Hb F-Augusta GA [Gγ59(E3)Lys → Arg; HBG2: c.179A > G] and the other one is Hb F-Port Royal-II [Aγ125(H3)Glu → Ala; HBG1: c.377A > C].